A Review of Pollutant Concentrations in Urban Stormwater Across Eastern Australia, After 20 Years - Drapper, Darren; Olive, Kent; McAlister, Tony; Coleman, Rhys; Lampard, Jane-Louise (Frontiers in Environmental Chemistry, 2022)
Concerns about pollutants in urban stormwater were initially raised in the early 1970s. Australian investigations decades later, also found urban stormwater runoff contained elevated levels of sediment and nutrients, as well as heavy metals, that brought stormwater management to the forefront for regulators. Planning policies were implemented to integrate stormwater management into development in the form of water sensitive urban design (WSUD), also known internationally as low-impact design (LID) and Sustainable Urban Design solutions (SUDs). Since their introduction, comprehensive broad scale field research to verify their success in achieving load reduction targets (LRTs), has been limited. Paucity of field data on the performance of WSUD has prompted organisations to initiate their own locally-specific studies. Limited regulatory guidance on design of monitoring programs has resulted in various methodologies and meta-data recording. This research review collates urban stormwater data from 77 Australian studies, from geographic regions of east coast Australia. The raw dataset in this review included 2,836 events and 4,536 individual results, collected between 1993 and 2021 from local councils, research organisations and water authorities. The review examined total suspended solids (TSS), total phosphorus (TP) and total nitrogen (TN) concentrations, prior to any form of treatment measures as they are the focus of current guidelines and standards for stormwater management. Seminal research, used to inform stormwater guidelines and water quality modelling across Australia, is significantly different (p < 0.001), in this case approximately double the reviewed concentrations. International data is also >20% higher, on average. Geographic location of catchments had the greatest influence on pollutant concentrations, after accounting for the effects of land use and catchment urbanisation date (p < 0.001). Based on the findings of this review, generic load reduction targets (expressed as a percentage of annual inputs, e.g. 80% TSS reduction, 45% TN, 45% TP) typical in current Australian planning regulations, may be sub-optimal in achieving receiving water quality goals, particularly given the difficulty of removing pollutants when present in low concentrations. Alternately, place-based discharge targets which meet, or exceed, background water quality, or ecological and hydrological benchmarks may be a more appropriate tool to achieve environmental objectives.